2004
DOI: 10.1073/pnas.0403248101
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical crypsis in the avoidance of natural enemies by an insect herbivore

Abstract: Plant-herbivore interactions provide well studied examples of coevolution, but little is known about how such interactions are influenced by the third trophic level. Here we show that larvae of the specialized lepidopteran herbivore Heliothis subflexa reduce their vulnerability to natural enemies through adaptation to a remarkable and previously unknown feature of their host plant, Physalis angulata: The fruits of this plant lack linolenic acid (LA), which is required for the development of most insects. By ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 31 publications
4
47
0
Order By: Relevance
“…Another form of antipredator adaptation also involves olfactory emissions (chemical crypsis) (3). We might here speculate that, in the presence of a predator, the production of alarm pheromones, such as SBT (63), not only signals danger to conspecifics but also induces freezing and might also modify the prey scent, which could fool the predator by mimicry of its own scent (2,3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another form of antipredator adaptation also involves olfactory emissions (chemical crypsis) (3). We might here speculate that, in the presence of a predator, the production of alarm pheromones, such as SBT (63), not only signals danger to conspecifics but also induces freezing and might also modify the prey scent, which could fool the predator by mimicry of its own scent (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple hiding strategies (crypsis) coexist and are best when combined. Indeed, crypsis can be morphological when the prey uses its body shape/color to blend into the background (camouflage), it can be behavioral when the prey uses immobility or subtle steady movements to decrease the chance of being detected (freezing); or it can be chemical when the prey releases odorant molecules to mask its own odor (2,3).…”
mentioning
confidence: 99%
“…Numerous studies have shown that this ingenious plant defense system is triggered by substances in the regurgitants of the herbivores. The best known of these plant volatile elicitors are the fatty acid amino acid conjugates (FACs) that first were identified from beet armyworm, Spodoptera exigua, larvae (3) but later also found in several other lepidopteran species (4)(5)(6)(7)(8) and other insects (9,10). Of the FACs, volicitin [N-(17-hydroxylinolenoyl)-L-glutamine], is the most active elicitor for seedlings of most cultivars of Zea mays (3,11,12).…”
mentioning
confidence: 99%
“…The ammonia assimilation into FACs was studied by liquid chromatography-mass spectrometry (LCMS) analysis of regurgitant obtained from S. litura larvae treated with artificial diets enriched with [ 15 N]NH 4 Cl and glutamic acid. The labeling ratios for FACs calculated from area values of extracted ion chromato- 18.1 Ϯ 0.3% for volicitin, and 16.7 Ϯ 0.4% for N-(17-hydroxylinoleoyl)-L-glutamine.…”
mentioning
confidence: 99%
“…Many investigations have been realised in order to understand the strength of interactions among species within natural communities [28]. Other organisms, such as herbivores reduce their vulnerability to natural enemies through adaptation to host plants [29].…”
Section: An Analogy Between Crime and Biological Situationsmentioning
confidence: 99%